Avaliação da estabilidade dimensional, flexibilidade e resistência à torção de instrumentos rotatórios de NiTi Twisted File e RaCe - Ligia Carolina Moreira Braga (2010)
The mechanical properties of the endodontic instruments are affected by factors such as diameter, design, chemical composition and thermo-mechanical treatments applied during the manufacturing process. The main goal of this work was to assess the flexibility and torsional resistance of the NiTi Twisted File (TF) and RaCe instruments with similar transversal section designs, however produced using different processes. The chemical components have all been analyzed with X-Ray energy spectroscopy (EDS), the present phases determined by X-Ray Diffractions (DRX) and the transformation temperatures obtained with differential scanning calorimeter (DSC). Images from the longitudinal and transversal sections were used for determining the diameter and the area 3mm away from the tip (D3 and A3), the position where the mechanical requests are focused on during the clinical use and the instruments are apprehended in the tests. The mechanical behavior has been evaluated through simulation of flexion and torsion until rupture accordingly to the ISO 3630-1. The TF and RaCe instruments have presented an alike chemical composition and only the phase to the environment temperature. The pairs of instruments, TF 25/0.06, RaCe 25/0.04 and TF 25/0.08, RaCe 25/0.06 have presented similar D3. A similarity of A3 values in TF 25/0.06 and RaCe 25/0.04 has been verified, as well as a substantial statistic difference between the instruments TF 25/0.08 and RaCe 25/0.06. The TF instruments have been shown to be more flexible, possibly due to thermal treatment they have undergone resulting in a softening of the alloy. The instruments TF 25/0.06 have presented values of maximum torque significantly superior to those from the instruments RaCe 25/0.04 despite their corresponding D3 and A3 values. Nonetheless, the instruments TF 25/0.08 and RaCe 25/0.06 have not shown any significant statistic differences regarding the resistance to torsion, even though the values of A3 of RaCe are considerably higher than the ones of TF. The disparities in dimensional characteristics might have influenced the reduction of the torsional resistance in RaCe instruments.